2018
DOI: 10.3389/fpsyg.2018.00555
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian “Digital Border Defense” and Competence for the Unforeseen: A Grounded Theory Approach

Abstract: Strategic Competence Leadership (SCL) is a tool meant to ensure that the Norwegian Armed Forces Cyber Defence (NAFCD) has the necessary expertise to cope with current and future unforeseen events. This is necessary in order to develop a better digital border defense against digital threats from different state or non-state actors. Unforeseen cyber incidents include for instance “zero-days” attacks and similar severe threats. The goal of the SCL in the NAFCD is the development of a reliable “Cyber Resilience.” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
13
0
2
Order By: Relevance
“…The case study presented by Coutu (2000), highlights the need to establish a profitable exchange relationship between leaders of people-oriented (e.g., sales), and IT functions, in order to create a cross-functional and cross-skill contamination. Systematic knowledge dissemination from the individual to the group is highlighted as the most effective way to spread knowledge and expertise across the organization (Boe and Torgersen, 2018). Coutu (2000) addresses how this cross-skill contamination can be performed, by means of implementing reverse-mentoring programs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The case study presented by Coutu (2000), highlights the need to establish a profitable exchange relationship between leaders of people-oriented (e.g., sales), and IT functions, in order to create a cross-functional and cross-skill contamination. Systematic knowledge dissemination from the individual to the group is highlighted as the most effective way to spread knowledge and expertise across the organization (Boe and Torgersen, 2018). Coutu (2000) addresses how this cross-skill contamination can be performed, by means of implementing reverse-mentoring programs.…”
Section: Resultsmentioning
confidence: 99%
“…Studying modern military operational environments, Boe and Torgersen (2018) highlight the need to lead under volatile, uncertain and complex situations, characteristics they find similarly describe the context of modern e-businesses. According to the authors, leadership training needs to combine both technology and change, creating simulations of scenarios in which ambiguous information and improvisation create complex and uncertain conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Grounded theory uses induction-related procedures that generate an explanatory theory of the phenomenon analyzed ( Glaser and Strauss, 1967 ). In this study, we emphasize a conceptual and theoretical approach based on grounded theory ( Boe and Torgersen, 2018 ), since concepts and data relationships are continuously produced and reexamined to be considered rigorous as scientific research ( Strauss and Corbin, 1998 ). Linked to symbolic interactionism, grounded theory ensures to know what is happening and why in a social group ( Strauss and Corbin, 1990 ) to formulate grounded theories with empirical analysis ( Martin and Turner, 1986 ; Strauss and Corbin, 1990 ; Andrade-Rhor, 2019 ) on human behavior and the social world ( Kendall, 1999 ).…”
Section: Methodsmentioning
confidence: 99%
“…Common to the theses is that they largely point to the distance between the strategic management documents that are advocated by the NAF leadership and what is practiced in the organization. As mentioned before, even the NAF Cyber Defense has been found to struggle with issues such as strategic competence leadership, organizational structures, competence development, needs, plans, handling and communication (Boe and Torgersen, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The NAF is an organization that for several years already has introduced digital systems that allow top management to follow operations from a distance and even have the ability to directly influence and intervene in the events while they are ongoing (Forsvarsstaben, 2014). On the other hand, research has shown that even a highly digitized part of the NAF, the NAF Cyber Defense, struggles with strategic competence leadership, organizational structures, competence development, needs, plans, handling and communication (Boe and Torgersen, 2018). The Norwegian military education has not been exposed to the very big upheavals until now.…”
Section: Introductionmentioning
confidence: 99%